Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.jmapro.2020.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of solidification in die casting using numerical simulations and machine learning

Abstract: In this paper, we demonstrate the combination of machine learning and three dimensional numerical simulations for multi-objective optimization of low pressure die casting. The cooling of molten metal inside the mold is achieved typically by passing water through the cooling lines in the die. Depending on the cooling line location, coolant flow rate and die geometry, nonuniform temperatures are imposed on the molten metal at the mold wall. This boundary condition along with the initial molten metal temperature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Miller demonstrated in a 1-D model to challenge common notions of how many cycles it takes to attain a quasi-steady state [50]. Other studies, especially modeling-based investigations, have shown that die temperature is a high impact parameter on castings and the dies themselves [51][52][53][54]. For these reasons, a robust and reliable method of collecting the die temperature is the next source of data to drive predictive modeling forward.…”
Section: Results Of Neural Network Regression Methodsmentioning
confidence: 99%
“…Miller demonstrated in a 1-D model to challenge common notions of how many cycles it takes to attain a quasi-steady state [50]. Other studies, especially modeling-based investigations, have shown that die temperature is a high impact parameter on castings and the dies themselves [51][52][53][54]. For these reasons, a robust and reliable method of collecting the die temperature is the next source of data to drive predictive modeling forward.…”
Section: Results Of Neural Network Regression Methodsmentioning
confidence: 99%
“…Finally, in a number of previous papers on metal manufacturing, several optimization techniques, such as the genetic algorithm, [131][132][133][134] particle swarm optimization, 46,135 Bayesian optimization, [136][137][138] and even statistical approaches like response surface methodology, 17,139,140 Taguchi's design of experiment, and analysis of variance (ANOVA), [141][142][143] have been used. The main difference between these methods and the RL is that the former do not ''learn from experience.''…”
Section: Process Optimizations For Manufacturing Mmcs Using Reinforcement Learningmentioning
confidence: 99%
“…Based on these results, the molten metal flow systems are modified, which leads to improvements of the process and deepened knowledge about the phenomena of flow in casting processes. An approach for multi-objective optimization of the solidification of casting processes is shown in [29] by using machine learning combined with process simulations.…”
Section: Combining Structural Optimization and Process Assurancementioning
confidence: 99%